A study on effect of schooling status and oral hygiene education on early childhood caries of the paediatric patients attending students’ polyclinic, Kulliyyah of Dentistry, IIUM Kuantan - Ahmad, Umme Hafizah; Mohd Salleh, Nor Aini; Sukmasari, Susi (Kulliyyah of Dentistry, 2011)
Objective: To compare decayed and filled (dfl index and severity of early childhood caries (ECC) between children who are attending preschool and are not attending preschool. Materials and Mefiod: A cross- sectional comparative study was conducted amongst 50 paediatric patients aged from 2- to 6-years old. Their caries statuses were evaluated using World Health Organization NIrHO) diagnostic criteria for decayed and filled teeth. A semi structured questionnaire was used to collect data by interviewing the caregivers. Analysis was done using SPSS version 16.0. X and independent pair "t' test were used. Results: In the study, 80% (40) of the children attend preschool. Among them, only 28 children obtained Oral Hygiene Education (OHE) at school. Minimum, maximum and mean t (SD) of df values of the children were 0, 20 and 10.58 t (5.1) respectively. Only 2 children ( 4,%) were caries free (df :0) ; 6 children (12%) were moderate-ECC ( df <S) ; 42 children (847") were severe-Ecc al > 5). This study proved the disease pattern; most of the caries are in maxillary central incisors and mandibular first primanr molar. There were no significant association (p>0.05) benryetn severig' of ECC with schooling stahrs including age, gender, tvDes and frequency of receiving OHE" C,,mcfusirx- No significant association betrreen schooling status, types and frequency receivlng OHE and occurrence of sel'erity of ECC. Other factors may influence the occurrence of caries in children rather than schooling shfus and effectiveness of OHE. Caries status was distant from the WHO oral health taryet of 50% caries free in this age range.